ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI TINGKAT PARTISIPASI MASYARAKAT DALAM PELAKSANAAN PROYEK P2MPD DI KABUPATEN TUBAN - Farid Achmadi; R Sutjipto; Vita Ratnasari (Jurnal Teknobisnis, 2005)
Multi-dimensional crisis at the end 1997 has brought a very strong impact to social and economic aspects of community, resulting in fast increase in the number of unemployment and poor people as well as social structure damage that hamper development pace of the Republic of Indonesia. The aforesaid condition has made us aware of the importance of having economy which is based on community as the power. The community empowerment program is required as the follow-up action against the above mentioned impact.Implementation of a program called “P2MPD” (Regional Government Administration and Community Empowerment Project) in Regency of Tuban has indicated critical points due to the differences of interest, so as to decrease the level of participation of the community. It is for this reason that this research was carried out with the intention to find out variables and factors affecting level of community’s participation as well as the factors that need to be improved in implementing the P2MPD program in Regency of TubanFrom the output analysis, it was found that the most dominant factor influencing level of participation of community in executing the P2MPD project in Regency of Tuban are democracy, transparency, security and the conducive social condition of community and the factors that require high improvement efforts are the competitors and facility factors